A study on risk factors, maternal and foetal outcome in cases of preeclampsia and eclampsia at a tertiary care hospital of South India - Sailaja, Bandaru; Cooly, Vijayalakshmi; Sailcheemala, Bhuvaneswari; Sailaja, Surayapalem (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Hypertension in pregnancy remains still a major health issue for women and their descendants throughout the world but remains a major issue in developing countries rather than developed countries. Eclampsia accounts for 24% of maternal deaths during pregnancy in India according to FOGSI study in India. Changing trends in pregnancy globally with increased maternal age of conception, assisted reproductive technologies has contributed a significant impact in the risk factors for PE and eclampsia. The present study was aimed to investigate and determine the related risk factors in cases of PE and eclampsia. The maternal and foetal outcomes with major complications of the women with PE and eclampsia were also studied. Methods: A prospective cross sectional study for a period of two years was conducted at a tertiary care hospital among antenatal cases and all cases of PIH were recorded and studied. Cases were managed as per the existing obstetric protocol after clinical examination and investigations. Detailed socio demographic data and history of risk factors were collected and entered into Microsoft excel sheet and analyzed. Maternal and foetal outcome were noted in the cases of the study. Results: The incidence of PE and eclampsia in the study was 43.3% and 10.8%, 25-35 years age group being the most common. PE and eclampsia was associated with BMI>30, parous women with previous history of PE, diabetes mellitus and more in unregistered cases. PE and eclampsia were more in Illiterates and socio economic class 2 &3. The incidence of maternal complications was 32.99% with premature labour being the common and in case of foetal complications prematurity was the commonest with 16 cases. The maternal mortality was very less with only 4.64% in the study. Conclusions: Pregnancy induced hypertension with PE and eclampsia still remains a major problem in developed countries. Good antenatal care with increased awareness and increased antenatal visits may help in reducing the incidence and maternal and foetal complications. Increased incidence among illiterates and low socio economic status group provides the target group to be directed against any medical measures and national health programmes.